A81: Spectrum of Mevalonate Kinase Deficiency: Is Colitis More Common Than We Think?. Issue 11 (March 2014) - Biggs, Catherine; Dedeoglu, Fatma
Abstract : Background/Purpose: Mevalonate kinase deficiency (MKD) is an autosomal recessive inflammatory disorder caused by a mutation in the mevalonate kinase (MVK) gene. This leads to decreased enzymatic activity, resulting in impaired cholesterol biosynthesis and increased production of inflammatory mediators such as interleukin 1‐β. There are two known forms of MKD, with Hyperimmunoglobulinemia D Syndrome (HIDS) carrying a milder phenotype and Mevalonic Aciduria (MA) representing a severe form. HIDS is characterized by recurrent febrile episodes accompanied by varying clinical features that include lymphadenopathy, gastrointestinal symptoms, oral ulcers, and arthralgia. A recent report identified early onset colitis as a feature of MKD in two patients (Levy M et al, 2013). Here we report the clinical and laboratory phenotypes of patients cared for at Boston Children's Hospital who were diagnosed with HIDS/MKD. Methods: We conducted a retrospective chart review of children with HIDS/MKD treated from 2002–2012 at the Rheumatology Clinic at Boston Children's Hospital. Charts were first identified by searching for key words or billing codes related to autoinflammatory syndromes. A manual chart review was then performed to confirm appropriate case identification. Results: Four patients were diagnosed with HIDS/MKD over the 10‐year period. Age of symptom onset varied from 2 months to 1 year. Fever duration ranged from 1–5 days, with duration between fevers ranging from 9 days to 12 weeks. Symptoms included sore throat, oral lesions, vomiting, diarrhea, abdominal pain, rash, and arthralgia. Prodromal symptoms were identified in all patients, and included irritability, anorexia, fatigue, geographic tongue, rash, and neck pain. Three of the four patients had a history of bloody stools beginning in infancy/early childhood, and were followed by gastroenterology. All patients had lymphadenopathy on exam, and splenomegaly was detected in two patients by ultrasound. Labs obtained during febrile episodes showed elevated inflammatory markers, however, in two out of three patients evaluated in between fevers, the ESR was persistently elevated. All four patients had elevated IgA when compared to age matched normal values, and two patients had elevated IgD levels. Genetic testing was performed in all patients, with all four having two heterozygous mutations within the MVK gene. In addition, one patient also had single variant mutations of unclear significance in two other genes associated with autoinflammatory syndromes. Two patients were treated with steroids and in each case this aborted febrile episodes, however, in one patient steroid use was also associated with increased fever frequency. One patient had decreased severity of symptoms when treated with colchicine as well as with montelukast, and had rapid resolution of fever and associated symptoms when treated with anakinra. Conclusion: The persistence of ESR elevation outside of febrile episodes seen in patients with HIDS/MKD may indicate the presence of chronic subclinical inflammation. Hematochezia was commonly seen, and could indicate the presence of colitis. Of the immunomodulatory medications used in this small patient population, anakinra appeared to be effective.